Digital Transformation in the Use of Artificial Intelligence Technology for Inclusive Islamic Education at MAN 2 Pandeglang - Aat Royhatudin; Agus Hidayatullah; Siti Inayatulloh (CV. Creative Tugu Pena, 2026)
This study investigates the process and impact of digital transformation through the adoption of Artificial Intelligence (AI) technology in fostering inclusive Islamic education at MAN 2 Pandeglang. In the contemporary educational landscape, the integration of technology plays a crucial role in creating equitable learning environments that address diverse student needs, including those with disabilities, varying learning paces, and diverse socio-cultural backgrounds. This research explores how a traditional Islamic educational institution navigates the transition toward a technologically enhanced and inclusive pedagogical approach. Using a qualitative case study design, data were collected through in-depth interviews with school administrators and teachers, classroom observations, and analysis of institutional policy documents. The findings reveal that MAN 2 Pandeglang has implemented several AI-driven initiatives as part of its digital transformation strategy. Key applications include: (1) AI-based adaptive learning platforms that personalize the delivery of Islamic and general subjects according to individual student abilities; (2) Natural Language Processing (NLP) tools, such as speech-to-text and text-to-speech technologies, to assist students with visual or hearing impairments in accessing Qur’anic studies and other textual materials; and (3) AI-powered learning analytics used to identify students at risk of learning gaps, enabling proactive and targeted educational support. The study concludes that digital transformation through AI technology significantly enhances the inclusivity of Islamic education at MAN 2 Pandeglang by reducing barriers to access and participation. It promotes a more engaging, personalized, and equitable learning experience aligned with the Islamic principles of justice ('adl) and compassion (rahmah). However, the transformation also presents several challenges, including the need for continuous teacher training, adequate technological infrastructure, and careful consideration of ethical issues related to AI implementation. This research contributes to the growing body of literature on technology integration in religious education and offers a practical model for other Islamic educational institutions seeking to leverage AI to create more inclusive learning environments.